(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: Trich omonas vaginalis is a parasite that is found worldwide, with infection rates approaching 30% in some areas. It is transmitted through sexual contact and direct use of other people’s tools. The aim of this study is to diagnose Trichomonas vaginalis parasitic infection in Al-Muthanna province. Materials and Methods: From the beginning of October 2024/10/27 to February 2025 2/2 a diagnostic study was conducted to investigate the presence of Trichomonas vaginalis in patients visiting the Teaching Maternity and Obstetrics Hospital and private gynecological clinics, as well as in local pathological analysis laboratories in the province. Results: A total of 100 samples were examined, showing the highest infection rate among females (72.61%), with the age group 21–25 years most affected (32.14%). Married women had higher infections (59.02%) than unmarried (40.98%), and non-pregnant women showed higher rates (52.46%) compared to pregnant (47.54%). Infections were more common in rural women (53.58%) than urban (46.42%), and highest among women with primary education (35.72%) versus the lowest in university graduates (9.51%). White to gray vaginal discharge represented the highest percentage (78.57%), while brown discharge was the lowest (2.38%). Conclusion: This diagnostic study highlights the high prevalence of parasitic infections among women more than men, emphasizing the urgent need to enhance awareness and health education in this side. The results indicate that younger and married women are particularly vulnerable to infection, which necessitates intensified efforts to educate these groups about the risks associated with such infections and effective prevention measures